Natural dynamics and thinning response of young lenga [Nothofagus pumilio] trees in secondary forests of Southern Patagonia = Dinámica natural y respuesta al raleo de árboles juveniles de lenga (Nothofagus pumilio) en bosques secundarios en Patagonia Sur - Peri, Pablo Luis; Martínez Pastur, Guillermo José; Monelos, Lucas H. (2017)
For saw-log production, planned thinning in secondary forests may reduce the time to yield products of a desired size and quality. To explore some options, long-term monitoring plots were established in 1996 in two secondary stands of Nothofagus pumilio (19,300 stems ha-1, age 34 years and 18,300 stems ha-1, age 40 years) in Santa Cruz province, Argentina. The study quantified growth responses to different thinning intensities around crop trees in the understory stratum of a two-aged stand, and growth dynamics in a natural unthinned stand regenerated by strip clearcutting. For the analysis of natural dynamics, growth, mortality and shift of crown classes of all trees were measured annually during 10 years. For thinning, 1,111 crop trees per hectare were selected. Thinning consisted of four intensities: elimination of one (T1), two (T2) and all (Tt) effective competitors, and a control (Tc). Each treatment was replicated ten times in a split plot design, where the main plots in this two-aged stand were three different levels of canopy covered by the remaining overstory seed trees (0, 12 and 33 %). The stand dynamics among unthinned plots revealed that competition-induced mortality occurred at a mean rate of 680 trees ha-1 year-1 (3.5 % of all trees) and mean growth rate of 7.2 m3 ha-1 year-1. Ten-year results from the thinned plots indicated a significant difference in the growth response of crop trees among treatments; being higher for Tt and T2, and under 12 % canopy cover. Thinning also reduced windthrow because it removed only the effective competitors and maintained a high stocking among crop trees. That offered mutual protection within the understory stratum.